Analisis Faktor-Faktor yang Mempengaruhi Behavioral Intention dan Use Behavior Pada Pengguna Aplikasi Mobile Banking BRImo Menggunakan Model UTAUT 2 (Unified Theory of Acceptance an Use of Technology 2) - Ludi Priyadi; Arnold Ropen Sinaga; Titan Parama Yoga (Universitas Informatika dan Bisnis Indonesia, 2025)
This research is based on the problem of users who complain or are less comfortable in using services on BRImo Mobile Banking. Although BRImo Mobile Banking is recognized as having a good ability to provide information, the inconvenience from the user's side can reduce user confidence in the service. This study aims to determine the intention and use of digital services of BRImo Mobile Banking application in Bandung using behavioral intention and use behavior as factors that influence the technology acceptance model (UTAUT2). The research method is quantitative, analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with 249 research respondents. The results showed that the performance expectancy variable on behavioral intention had a positive and insignificant effect. Other variables such as effort expectancy, social influence, facilitating conditions and habit on behavioral intention have a positive and significant effect. There are also facilitating conditions, habit and behavior intention variables on use behavior, which have a positive and significant effect.